Identification of Potential Vectors and Detection of Rift Valley Fever Virus in Mosquitoes Collected Before and During the 2022 Outbreak in Rwanda - Isidore Nsengimana; Emmanuel Hakizimana; Jackie Mupfasoni; Jean Nepomuscene Hakizimana; Augustino A. Chengula; Christopher J. Kasanga; Gillian Eastwood (Pathogens)
Rift Valley fever virus (RVFV) is an emerging mosquito-borne arbovirus of One Health importance that caused two large outbreaks in Rwanda in 2018 and 2022. Information on vector species with a role in RVFV eco-epidemiology in Rwanda is scarce. Here we sought to identify potential mosquito vectors of RVFV in Rwanda, their distribution and abundance, as well as their infection status. Since an outbreak of RVF occurred during the study period, data were obtained both during an interepidemic period and during the 2022 Rwanda RVF outbreak. Five districts of the eastern province of Rwanda were prospected using a combination of unbaited light traps and Biogents (BG Sentinel and Pro) traps baited with an artificial human scent during three periods, namely mid-August to mid-September 2021, December 2021, and April to May 2022. Trapped mosquitoes were morphologically identified and tested for viral evidence using both RT-PCR and virus isolation methods on a Vero cell line. A total of 14,815 adult mosquitoes belonging to five genera and at least 17 species were collected and tested as 765 monospecific pools. Culex quinquefasciatus was the most predominant species representing 72.7% of total counts. Of 527 mosquito pools collected before the 2022 outbreak, a single pool of Cx. quinquefasciatus showed evidence of RVFV RNA. Of 238 pools collected during the outbreak, RVFV was detected molecularly from five pools (two pools of Cx. quinquefasciatus, two pools of Anopheles ziemanni, and one pool of Anopheles gambiae sensu lato), and RVFV was isolated from the two pools of Cx. quinquefasciatus, from Kayonza and Rwamagana districts, respectively. Minimum infection rates (per 1000 mosquitoes) of 0.4 before the outbreak and 0.6–7 during the outbreak were noted. Maximum-likelihood phylogenetic analysis indicates that RVFV detected in these mosquitoes is closely related to viral strains that circulated in livestock in Rwanda and in Burundi during the same RVF outbreak in 2022. The findings reveal initial evidence for the incrimination of several mosquito species in the transmission of RVFV in Rwanda and highlight the need for more studies to understand the role of each species in supporting the spread and persistence of RVFV in the country.